A parallel algorithm to find the exact solution of the travelling salesman problem - Mohammed W. Al-Neama; Iman Abdulwahab Ahmed; Salwa M. Ali (Institute of Advanced Engineering and Science, 2023)
The traveling salesman problem (TSP) is a problem in computer science that has been extensively studied and has a wide variety of real-world applications. It is considered an NP-hard issue since the only way to get a precise solution to it is to wait an exponentially long amount of time unless P=NP. Both accurate and heuristic algorithms exist to tackle this problem. The Branch-and-Bound algorithm (BnB) is often regarded as the most significant precise approach, despite the fact that it traverses, in the worst scenario, all potential tours in order to calculate the tour efficiently. This study proposed an efficient parallel algorithm to solve TSP by using a cluster multicore system. An exact algorithm will be used to get the optimal solution, and to expedite the search for the best path, we have employed a multi-threaded approach that capitalizes on the processing power of multiple CPU cores to concurrently process sub-problems.